Suppurative splenitis in a filly - Daneze, Edmilson R.; Montello-Neto, Joel S.; Moraes, Angélica T. B.; Magalhães, Geórgia M.; Sousa, Brunna L. N.; Chicone, Adriano C. V.; Dias, Deborah P. M. (Brazilian Journal of Veterinary Pathology, 2018)
Splenic abscess is an uncommon condition in humans and animals. The present report describes a rare case of suppurative splenitis in a 14-month-old filly, presented with signs of mild colic, depression and hyporexia. After clinical and laboratorial evaluation, a suppurative process of undetermined location was suspected. Medical therapy and supportive care were initiated, general condition has degraded in few days, and a paracentesis was performed diagnosing peritonitis. Given the poor prognosis, euthanasia was elected. At necropsy, multiple splenic abscess and diffuse peritonitis were identified. The etiology was not determined.